The factors contributing to low schools enrollment of females in South Sudan - Ajak, Bol Elijah Bul (Archives of Community Medicine and Public Health, 2019)
This aimed to describe the factors contributed to low enrollments of female in school in South Sudan; these factors are either political reason, cultural reasons. The literature reviewed were from the related information from the prior researchers, their findings has significant to the females’ enrollments, but the failure of their researches was that, they recommended to the government only on the issues on how to reduced poverty. Poverty is not affecting only females, it affect both genders, and cannot be the main factor that cause low enrollment of female. As a result this paper has found it out that, the two mains factors that affect female enrollments was the negative behaviors of the people toward female education and lack of awareness of the South Sudanese communities about the government policies of encouraging females’ education. The recommendations were directed to the government of South Sudan to initiate an awareness campaigns to be conducted annually in the former ten states of the republic of South Sudan and also forms policy implementing group at local level of the government including villages, household, schools, stakeholders including chiefs and the parents, to understand the importance of female education, through this process, the communities can gradually change their behaviors toward female education.